Negative Politeness Strategies in â€The Menuâ€ Movie - Laila Marfirah; Afriana Afriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The aim of study discovers the different types of negative politeness methods is classified as descriptive qualitative research. The study's findings were derived from words recognized the character "The Menuâ€ as negative politeness techniques and analyzed using theory presented by Brown and Levinson (1987). The observation and non-participatory methods were used to collect data. In addition, the pragmatic identity method was employed to analyze the data. The findings of this study are as follows: 2 Be conveniently indirect, 4 Question and Hedge, 1 Be pessimistic, 1 Minimize the Imposition, 1 Give Deference,2 Apologize, 1 Impersonalize interlocutors, 1 State the FTA as general Rule, 1 Nominalize , 1 Go on record as incurring a debt , or as not indebting H. We have 15 negative politeness strategies overall. In The Menu Movie, the main character's refusal to connect with the other character became the most common technique. We have 15 negative politeness strategies overall. In The Menu Movie, the main character's refusal to connect with the other character became the most common technique.